(untitled) (Revista Justiça do Direito, 2019)
This article aims to analyze the potential impact of forced internal displacement on international refugee migration, considering the relation between internal and international migration: Are today’s IDPs tomorrow’s refugees? It is likely that many refugees were forcibly displaced in their own countries before applying for asylum. Therefore, to develop this investigation, this article is divided into three sections. In the first section, it presents a general approach about internally displaced persons (IDPs) and refugees, including definitions and the bases of its protection under international law. Afterwards, it analyzes data on international migration and on internal displacement. At the end, these data are compared and possible link between internal and international forced migration is analyzed.